(untitled) (Nigerian Journal of Physiological Sciences, 2025)
The rapid increase in aging population and age-linked cognitive impairment as well as dementia of Alzheimer’s type are becoming more prevalent globally. Genetic and environment interactions played key role in dementia pathology. Oxidative stress and cholinergic disruptions are well linked with dementia. Hence, phytochemicals with neuroprotective and antioxidant properties could help ameliorate mitochondrial dysfunction and toxic effects misfolded amyloid-beta and tau proteins in dementia of Alzheimer’s type. Previous studies have alluded to the beneficial action of hesperidin in mild cognitive impairment but delivery could be better enhanced in nanoparticulate form. Hence, this study sought to investigate the memory enhancing ability of hesperidin nanoparticles (HES_) on scopolamine-induced memory impairment in mice. Mice were randomly assigned into 6 groups (n=6) and treated as follows; vehicle only, vehicle + SCOP (1mg/kg, i.p.), HES (1,10 and 50mg/kg, p.o., respectively) + SCOP and donepezil (1mg/kg; p.o.) + SCOP for 14 consecutive days followed by behavioral assessment for memory function using open field test, Y-maze, novel object recognition and Morris water maze for locomotion, working, cognition and spatial learning, respectively. The animals were euthanized and brain samples were collected for biochemical assays (oxidative stress markers and acetylcholinesterase activity). SCOP or HES administration did not affect locomotor activity, however, SCOP reduced the percentage alternation behaviour in the Y-maze and discrimination index in NOR tests with no significant change in escape latency time in MWM task indicative of working memory, cognition and spatial learning impairment. In contrast, the pre-administration of HES produced a dose-dependent and significant increase in working memory, cognition and spatial learning abilities. Similarly, HES_ pretreatment reduced scopolamine-induced increase in lipid peroxidation and acetylcholinesterase activity and deficit in antioxidant enzyme activity in the hippocampus and prefrontal cortex caused by SCOP. The results of the present study further showed the potential of hesperidin in nanoparticle form in the enhancement of memory formation through the amplification of antioxidant defense and cholinergic neurotransmission.